2021
DOI: 10.3390/jfmk6030056
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Component Physical Activity Interventions in the UK Must Consider Determinants of Activity to Increase Effectiveness

Abstract: Interventions to increase physical activity in children have adopted broad approaches and achieved varying success. There is a need to adopt approaches underpinned with a theoretical basis. Accordingly, the aim here was to implement and evaluate a 12-week intervention designed using the concepts of the COM-B model to determine the effect this has on physical activity levels. One hundred and forty-seven school-age children (mean age 8.9 ± 1.3 years) took part in a 12-week program delivered in a school setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…These methods should understand the contextual differences in the needs, experiences, and attitudes of older adults participating and not participating in sport. Further, consistent with research [53][54][55], the present analysis found that indices of multiple deprivation are inversely associated with sports participation. Barriers to participation in sport or physical activity stemming from deprivation include the provision of and access to facilities and public transport, reduced disposable income, health inequalities, and crime [53][54][55], factors likely exacerbated during the COVID-19 pandemic [12].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…These methods should understand the contextual differences in the needs, experiences, and attitudes of older adults participating and not participating in sport. Further, consistent with research [53][54][55], the present analysis found that indices of multiple deprivation are inversely associated with sports participation. Barriers to participation in sport or physical activity stemming from deprivation include the provision of and access to facilities and public transport, reduced disposable income, health inequalities, and crime [53][54][55], factors likely exacerbated during the COVID-19 pandemic [12].…”
Section: Plos Onesupporting
confidence: 90%
“…Further, consistent with research [53][54][55], the present analysis found that indices of multiple deprivation are inversely associated with sports participation. Barriers to participation in sport or physical activity stemming from deprivation include the provision of and access to facilities and public transport, reduced disposable income, health inequalities, and crime [53][54][55], factors likely exacerbated during the COVID-19 pandemic [12]. In addressing these societal challenges to accessing opportunity, Sport England (i.e., Uniting the Movement) and UK Government (i.e., Get Active) strategies place emphasis on the importance of place-based approaches to target those most at need and whole-systems models which encourage collective working (e.g., local delivery pilots).…”
Section: Plos Onesupporting
confidence: 90%
“…There is limited evidence to suggest that they will increase lifelong participation, with both positive and negatives of implementation still remaining to be fully established [50]. Improving PA rates amongst children is repeatedly targeted and well documented in various health strategies around the globe because of an increasing Western "obesity epidemic" [51]. In England, the National Health Service (2018, [52]) established that 20% of children aged 10-11 years old were classed as obese with rising levels for children across the primary school years.…”
Section: Setting the Pe (And Sport) Landscapementioning
confidence: 99%